ESTIMATION OF WAVE CHARACTERISTICS IN EAST VIETNAM SEA USINGWAM MODEL - Mau, Le Dinh; Tuan, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2014)
WAM (WaveModeling) is a third generation wave model developed by WAMDI Group which describes the evolution of a two-dimensional ocean wave spectrum under the effects of winds, currents, bottom and non-linear wave-wave interactions. The model runs for deep and shallow waters and includes depth and current refraction. This study used the WAM cycle 4.5 with model domain which is covered from 990E to 1210E and 00N to 250N with a resolution of ∆X = ∆Y = 0.250. Bathymetry of East Vietnam Sea (EVS) was taken from ‘ETOPO5’ data set of National Geophysical Data Center, Colorado, USA with resolution of 5’ (≈ 9 km). Wind velocities were obtained from 6 hourly NCEP/NCAR reanalysis data, USA with resolution of ∆X = ∆Y = 0.250. Study results show that during NE monsoon period, the main wave direction in EVS was NE and vice versa during SW monsoon period. Regions of greatest wave height were in the central and northern part of the EVS. Statistic of computed wave characteristics from 1987 to 2011 shows that wave regime in the offshore region of Nhatrang coast has two main wave directions that are NE with 40.82% of occurrence, SSW with 20.15% of occurrence. NE monsoon wave dominated from October to April of the next year, SW monsoon wave dominated from June to August. May and September are transitional periods. Assimilation of wind data with resolution of ∆X = ∆Y = 0.250 permits the model to be used to simulate the wave field during typhoon activity in EVS.